Updating of topographic maps in Nepal - Shrestha, Kalyan Gopal (Journal on Geoinformatics, Nepal, 2009)
The latest Topographical maps in Nepal are over a decade old. The “ideal” mapping product is one which is produced in real time from an updated spatial database. There is an urgent need to update existing ones. A complete and renewed process of updating databases, in traditional and conventional methods, is expensive, time-consuming and demands a great deal of human and capital resources. Therefore, it is impossible to update maps quickly by traditional and conventional methods. The Topographical Survey Branch of Survey Department is updating topographical maps using satellite imagery. It is preferable to focus on the continuous updating of the spatial database, with well defined specifications. In this paper, the updating of topographical maps in Nepal using satellite imagery is discussed.